Antimicrobial Activity of Tropical Soft Corals Found in the Northern Straits of Malacca - Hana, Marican; Raihana Z., Edros; Mahadi, Mohammad; Sazlina, Salleh (Penerbit Universiti Malaysia Pahang, 2016)
The study was conducted to obtain and test crude extracts from soft corals found at Pulau Payar, an island off the northern Straits of Malacca. Specimens were extracted in an equal volume of methanol and dichloromethane. The samples were then concentrated to obtain crude extracts. Anti-bacterial activities of the crude extracts were tested by disc diffusion method, minimum inhibition concentration (MIC) and minimum bacterial activities (MBC) assays. Out of twelve crude extracts tested, 50 percent of them showed inhibition for Staphylococcus aureus and MRSA; and approximately 8 percent have showed inhibition for Enterococcus raffinosus. The MIC of each extract is stated in the tables below. Only one of them showed bactericidal properties against MRSA. Soft corals around the world, have been found to contain beneficial chemical compounds, however not much research has been done in the region. This shows that soft coral extracts found in the Northern Straits of Malacca do have antibacterial potential, and this potential can be harnessed for future pharmaceutical exploration.